Pharyngoconjunctival fever. Issue 12 (December 1984) - Giladi, N; Herman, J
Abstract : Sixteen infants and toddlers from four kibbutz day nurseries contracted an illness comprising fever, conjunctivitis, respiratory infection, lymphadenopathy, otitis media, and a new sign, migratory palpebral erythema. Adenovirus type 3 was isolated from the pharynx of the first three children taken ill.